2014
DOI: 10.7567/jjap.53.04er05
|View full text |Cite
|
Sign up to set email alerts
|

Surface-activated-bonding-based InGaP-on-Si double-junction cells

Abstract: A fiber-bulk hybrid Er:YAG laser with the 1617 nm single frequency (SF) laser output is reported. The pump source was a 1532 nm Er,Yb fiber laser. Two intra-cavity etalons were used to obtain the SF operation at 1617 nm. Up to 640 mW SF output at 1617 nm was obtained, with a slope efficiency of 36.02%. 1532 nm fiber laser Fiber L1 L2 Input mirror Uncoated etalon Er:YAG Coated etalon Output coupler 1617 nm output

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In conclusion, Al0.2Ga0.8As//Si tandem solar cells has been demonstrated using SAB showing improved efficiency compared to its AlGaAs and Si stand-alone counterparts. A power conversion efficiency of 17% under one-sun AM1.5G spectrum was measured, which is higher than the present record for a wafer-bonded 2J III-V on Si solar cell [8]. Moreover, this performance level can be further improved by solving the following issues: a) non-optimum ARC, b) Si and AlGaAs material quality, c) front contact processing and inverted growth difficulties and d) over-thick GaAs bonding layer.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In conclusion, Al0.2Ga0.8As//Si tandem solar cells has been demonstrated using SAB showing improved efficiency compared to its AlGaAs and Si stand-alone counterparts. A power conversion efficiency of 17% under one-sun AM1.5G spectrum was measured, which is higher than the present record for a wafer-bonded 2J III-V on Si solar cell [8]. Moreover, this performance level can be further improved by solving the following issues: a) non-optimum ARC, b) Si and AlGaAs material quality, c) front contact processing and inverted growth difficulties and d) over-thick GaAs bonding layer.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, a 2J III-V on Si solar cell has the potential to reach very high efficiencies and it could be more cost competitive compared to the 3J-MJSC due to the high cost of III-V additional epitaxial layers needed [7]. To our knowledge, the best efficiency reported so far for a wafer-bonded 2J III-V on Si solar cell under AM1.5G standard spectrum is 11.1% achieved by Shigekawa et al with a GaInP//Si cell structure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the methods to construct III–V-on-Si architectures, a variety of studies have been reported. One of the most straightforward approaches would be the heteroepitaxial growth of GaAs-relevant materials on c-Si substrates; , however, despite the progress of elaborative buffer layer techniques to compensate for the difference in lattice constants and thermal expansion coefficients between GaAs and Si, the layer quality achieved with this type of approach remains a challenge. , Alternatively, bonding-based approaches have gained increasing attention, and as previously mentioned, impressive results have already been obtained by mechanically stacked four-terminal tandems and surface-activation-bonded two-terminal tandems. , We have also developed a unique semiconductor bonding strategy, termed smart stack. Using well-organized Pd nanoparticle (NP) arrays as bonding mediators, series-connected two-terminal tandem cells consisting of III–V and c-Si subcells have been successfully fabricated with the best efficiency of 30.8% . To make the smart stack technique more attractive, however, it would be preferable to find alternative materials for costly Pd, whose price has recently been rising due to the increasing demand of many other industrial applications…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] To overcome these issues, roomtemperature wafer-bonding techniques without high-temperature annealing have been applied for fabricating Si-based multi-junction solar cells such as AlGaAs ∥ Si, InGaP= GaAs ∥ Si, and InGaP ∥ Si solar cells. [22][23][24] Although Si solar cells have advantages such as low production costs and environmental loads, it is difficult to control band-gap energies on the basis of a specific current-matching condition to achieve higher efficiency. On the other hand, compound semiconductor solar cells do not have this disadvantage.…”
Section: Introductionmentioning
confidence: 99%